MORADIA COLETIVA: TRABALHANDO COM IDOSOS DA CASA LAR DE IJUI - OLEICNIZAK, ELISÂNGELA; RENNER, JULIANA; HILDEBRANDT, LEILA M.; LEITE, MARINÊS T.; PIOVESAN, SOLANGE M. S. (Salão do Conhecimento, 2013)
Resumo